Interface Engineering Strategies for Shuttle Mitigation in Alkali Metal–Sulfur Batteries: A Comparative Review from Li–S to Na–S and K–S Systems - Chen, Zihan; Yu, Qiyao; Wang, Wei; Zhang, Jianguo (Nano-Micro Letters, 2026)
Rechargeable alkali metal-sulfur (M–S) batteries, including Li/Na/K–S chemistries, have the potential to utilize abundant and low-cost sulfur cathodes yet offer high theoretical energy densities. However, their practical electrochemical performance is fundamentally limited by the polysulfide shuttle effect. This challenge is particularly exacerbated in Na–S and K–S systems owing to larger metal-ion radii, weaker solvation energies, slower redox kinetics, and greater electrolyte–electrode incompatibilities compared to Li–S batteries. This review presents a comparative analysis of interface engineering strategies designed to suppress the shuttle effect across these three systems. Following a summary of sulfur cathode properties and reaction mechanisms, we systematically examine the origins of polysulfide shuttling. Our analysis progresses from functional separator design and interlayer enhancements to the implementation of solid‑state electrolytes for root-cause inhibition. By evaluating interface engineering research specific to Na–S and K–S batteries, we elucidate both shared principles and unique challenges inherent to alkali M-S systems. Finally, we propose multifaceted solutions to achieve shuttle-free operation and enhance overall battery performance, thereby establishing a foundation for future advancements. Highlights: 1 The inherent differences and connections in interface engineering for inhibiting shuttle effects in alkali M (Li, Na, K)-S batteries are reviewed. 2 The research progress on the application of internal interface engineering in shuttle suppression is summarized. 3 The shuttle effect challenge analysis of Li-, Na- and K-S batteries and the prospect of the development direction of the next generation of alkaline M-S batteries are proposed.